Can peer mentoring improve online teaching effectiveness? An RCT during the COVID-19 pandemic - Hardt, David; Nagler, Markus; Rincke, Johannes (Labour Economics, 2022)
Online delivery of higher education has taken center stage but is fraught with issues of student self-organization. We conducted an RCT to study the effects of remote peer mentoring at a German university that switched to online teaching due to the COVID-19 pandemic. Mentors and mentees met one-on-one online and discussed topics like self-organization and study techniques. We find positive impacts on motivation, studying behavior, and exam registrations. The intervention did not shift earned credits on average, but we demonstrate strong positive effects on the most able students. In contrast to prior research, effects were more pronounced for male students<br
CRIS-Team Scopus Importer:2022-07-22
Keywords: Chancengleichheit

Tutoring in (online) higher education: Experimental evidence - Hardt, David; Nagler, Markus; Rincke, Johannes (Economics of Education Review, 2023)
Demand for personalized online tutoring in higher education is growing but there is little research on its effectiveness. We conducted an RCT offering remote peer tutoring in micro- and macroeconomics at a German university teaching online due to the Covid-pandemic. Treated students met in small groups, in alternating weeks with and without a more senior student tutor. The treatment improved study behavior and increased contact to other students. Tutored students achieved around 30% more credits and a one grade level better GPA across treated subjects. Our findings suggest that the program reduced outcome inequality. We find no impacts on mental health.
Created from Fastlane, Scopus look-up
Keywords: Covid-19; Higher education; Online education; Tutoring; Chancengleichheit

Who Does the Talking Here? The Impact of Gender Composition on Team Interactions - Hardt, David; Mayer, Lea; Rincke, Johannes (Management Science, 2024)
We analyze how the gender composition of teams affects team interactions. In an online experiment, we randomly assign individuals to gender-homogenous or gender-mixed teams of four. Teams meet in an audio chat room and jointly work on a team task that is gender-neutral in terms of individual productivity. By design, effects on team performance can only work through communication. We find that all-male teams communicate more than all-female teams and outperform teams of both alternative gender compositions. In mixed teams, men strongly dominate the team conversation quantitatively. Considering the ranking in terms of communication shares in mixed teams, we document that high-skilled men talk the most, followed by low-skilled men. High-skilled women talk more than low-skilled women, but much less than low-skilled men. We conclude that gender composition significantly impacts the way how teams exchange informatio